2019
DOI: 10.11646/zootaxa.4712.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Paleogene Verrucidae (Cirripedia: Verrucomorpha) of North America, with descriptions of three new species

Abstract: In North America, Paleogene Verrucidae are rarely encountered. Only a single named species has been previously discussed by Zullo & Baum (1979), who provisionally assigned a Palaeocene form from North Carolina to Verruca rocana Steinmann, 1921. Eocene deposits in Washington State (USA) have now yielded two new species from intertidal to shallow water environments: Verruca gailgoedertae sp. nov. from the middle Eocene Crescent/McIntosh transition zone, and Verruca sorrellae sp. nov. from the upper Eocene to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 482 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Deposition of the Gries Ranch Formation likely occurred under subtropical conditions (Dickerson 1917;Van Winkle 1918) at depths of less than 100 m according to Effinger (1938), although Hickman (1984) has suggested that the Gries Ranch fauna may have been transported into deep water. A verrucid barnacle recently described (Perreault & Buckeridge 2019) from the Gries Ranch fauna might support Hickman's suggestion; living verrucids can be found from 0-620 m (Buckeridge 1997) and most living species are found in the deeper end of that range. The age of the Gries Ranch Formation has been considered to be either late Eocene (Lindberg 1987) Description.…”
mentioning
confidence: 56%
“…Deposition of the Gries Ranch Formation likely occurred under subtropical conditions (Dickerson 1917;Van Winkle 1918) at depths of less than 100 m according to Effinger (1938), although Hickman (1984) has suggested that the Gries Ranch fauna may have been transported into deep water. A verrucid barnacle recently described (Perreault & Buckeridge 2019) from the Gries Ranch fauna might support Hickman's suggestion; living verrucids can be found from 0-620 m (Buckeridge 1997) and most living species are found in the deeper end of that range. The age of the Gries Ranch Formation has been considered to be either late Eocene (Lindberg 1987) Description.…”
mentioning
confidence: 56%